Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 10457 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Typhlops Oppel, 1811" ] } The dataset includes 10457 records from 102 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004526-150528172251762/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences